Respuesta :

Answer:

see explanation

Step-by-step explanation:

Calculate the distance (d) using the distance formula

d = √ (x₂ - x₁ )² + (y₂ - y₁ )²

with (x₁, y₁ ) = (4, 6) and (x₂, y₂ ) = (7, - 3)

d = [tex]\sqrt{(7-4)^2+(-3-6)^2}[/tex] ← expression for calculating distance

  = [tex]\sqrt{3^2+(-3)^2}[/tex]

  = [tex]\sqrt{9+9}[/tex]

  = [tex]\sqrt{18}[/tex] = 3[tex]\sqrt{2}[/tex]

Answer:

Step-by-step explanation:

note : distance between A(X1,Y1) an B (X2,Y2) is :  

AB= √((X2 - X1)² + (Y2 - Y1)²)

in this exercice : X1 = 4      X2 = 7   Y1 = 6    Y2 = -3  continue .....calculate AB